Perception of construction professionals to the performance of Nigerian quantity surveyors - A.E. Oke; I.O. Timothy; A.I. Olaniyi (Penerbit UKM, 2010)
The dynamism of the construction industry throughout the world call for no other skill of a professional quantity surveyor than the need for stringent cost control and effective cost management in providing value for money for construction clients. The aim of this research work is to examine the performance of Nigerian quantity surveyors with a view to ascertaining areas that need improvement. Primary data were collected via wellstructured close-ended questionnaire using the areas of competencies of quantity surveyors as identified by RICS. Percentile, mean internal score and Cronbach’s alpha test were employed in the analysis and testing of the hypotheses generated. The study revealed that Nigerian quantity surveyors are performing above average in all the identified areas of competencies of quantity surveyors from the perception of all the considered construction professionals. The study finally recommended a need for personal improvement by quantity surveyors in Nigeria – especially the older ones- in order to keep them abreast with the current trend in the construction industry.